Enviromental concerns - Das Gupta, Debabrata (Agrobios (India), 2011)
Environment has become the central point of global concern. The quality of environment is affected by production and consumption activities of people. Society's welfare with its economic activities is also governed by environment. Here, the convergence between ecology, ethics economics and other allied sciences obviously encompassing issues of environment has become the centre of our concerns. In such context this book on 'Environmental Concerns" concentrates.